Udayana One Health Collaborating Center (OHCC) initiated Bali’s first mass, integrated basic life support training - Sudewi, Anak Agung Raka; Budayanti, Nyoman Sri; Wiryana, Made; Senapathi, Tjokorda Gde Agung; Ryalino, Christopher; Pradhana, Adinda Putra (Bali Journal of Anesthesiology, 2019)
ABSTRACTBasic Life Support (BLS) is a first-aid training that can be utilized in case of emergency until the victims are retained by medical professionals. Mastering BLS skills can be the difference between life and death. A cardiopulmonary resuscitation (CPR) performed by a passer-by is important to ensure a successful resuscitation in out-of-hospital cardiac arrest. Yet, improving the survival rate for out-of-hospital cardiac arrest is still a major problem. Starting in 2019, Udayana One Health Collaborating Center (Udayana OHCC) will implement the first mass and integrated BLS training in Bali. The goals are to introduce BLS to more people and to produce BLS-friendly environment in Bali.